Taxonomic remarks on Pseudosempervivum (Brassicaceae) - Özüdoğru, Bariş; German, Dmitry (Phytotaxa, 2018)
The status of three names related to the genus Pseudosempervivum is reconsidered. As a result, Noccaea crassiuscula and Pseudosempervivum amanum are reduced to synonymy of P. sempervivum while P. gurulkanii is found conspecific with N. venusta. Problems in delimitation of P. sempervivum and P. aucheri are also briefly considered. The name Cochlearia sempervivum is lectotypified.